THE EFFECT OF STUDENT WORKSHEET BASED ON PREDICT OBSERVE EXPLAIN STRATEGY AGAINST THE LEARNING OUTCOMES - Oci Pitriyanti; I Dewa Putu Nyeneng; Nengah Maharta (Jurnal Pendidikan Matematika dan IPA, 2020)
The study was aimed to determine the influence of the use of student worksheet (LKPD) based on Predict Observe Explain (POE) strategy on student learning outcomes in the light material. This research was an experimental study with the design of experimental quasi using the form of a one-group pretest-posttest. The population of this study was the eighth-grade students of junior high school (SMP). Data analysis techniques were tested with the learning result grouping techniques, N-Gain analysis, hypothesis testing, linear regression tests, t-test paired test and effect size tests. The result of the N-Gain was a value of 0.60 with a moderate N-Gain interpretation.  Linear regression test result was obtained a coefficient value of 0.7, with the sig regression value of 0,0. The result of the paired t-test achieved a significance value of 0.0, which indicated that there was a raise prior and following treatment. The result of the effect size test was 0.31 with a medium interpretation. The learning outcomes for psychomotor learners had an average value of 3.52 with excellent interpretation. Based on these findings, it can be concluded that the POE strategy-based LKPD was considerably effective to be applied in schools resulting in an increasing effect of the students learning outcomes before and after the treatment of POE-based LKPD.